Effectiveness of The Jigsaw Learning Model in Chemistry Learning - Sabrina, Safira Afifah; Azzahroh, Syifa; Rahmawan, Setia (Universitas Papua, Manokwari, Indonesia, 2024)
This study evaluates the jigsaw learning model's efficacy for teaching chemistry. The Systematic Literature Review (SLR) method was the research methodology employed in this study. Data is gathered by documenting every article relevant to the inquiry. Seventeen publications from national journals were used in this study. The research findings led to the conclusion that the jigsaw learning model's efficacy in chemistry education can be used as a response to student issues to improve learning activities, learning outcomes, student motivation, and student achievement—all of which will contribute to raising the standard of education in Indonesia.